2019
DOI: 10.33307/entomon.v44i1.423
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution of Nilgiri grass yellow Eurema nilgiriensis Yata (Lepidoptera: Pieridae), with an updated taxonomic key to Eurema of Western Ghats, India

Abstract: Eurema nilgiriensis Yata, 1990, the Nilgiri grass yellow, was described from Nilgiris in southern India. There are not many published records of this species since its original description, and it was presumed to be a high-elevation endemic species restricted to its type locality. Based on the external morphology (wing patterns) as well as the male genitalia, the first confirmed records of the species from Agasthyamalais and Kodagu in the southern Western Ghats, is provided here. This report is a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…These sight records show that the species is very active during post-monsoon months, throughout the forested tracts of surveyed localities in Kannur, Kozhikode, Wayanad, Malappuram, and Palakkad districts of Kerala from elevations 60-1000 m in the Western Ghats. These records add to the recently published range extensions of this species from Kodagu District, Karnataka and Agasthyamalais, Kerala (Sujitha et al 2019). From the above field records and the records already published (Sujitha et al 2019), we presume that this species is active from September to May in the Western Ghats, October-November being the primary season.…”
Section: Range Extensionsupporting
confidence: 71%
See 1 more Smart Citation
“…These sight records show that the species is very active during post-monsoon months, throughout the forested tracts of surveyed localities in Kannur, Kozhikode, Wayanad, Malappuram, and Palakkad districts of Kerala from elevations 60-1000 m in the Western Ghats. These records add to the recently published range extensions of this species from Kodagu District, Karnataka and Agasthyamalais, Kerala (Sujitha et al 2019). From the above field records and the records already published (Sujitha et al 2019), we presume that this species is active from September to May in the Western Ghats, October-November being the primary season.…”
Section: Range Extensionsupporting
confidence: 71%
“…These records add to the recently published range extensions of this species from Kodagu District, Karnataka and Agasthyamalais, Kerala (Sujitha et al 2019). From the above field records and the records already published (Sujitha et al 2019), we presume that this species is active from September to May in the Western Ghats, October-November being the primary season. Males are often found engaged in mud-puddling along banks of streams and damp soil in well-wooded forests.…”
Section: Range Extensionsupporting
confidence: 71%
“…In India, the work on superfamily Pyraloidea was initiated by Hampson (1896) that included the distribution and taxonomy of 1,136 species. Up to date, a number of authors from India and across the globe have occasionally reported and described many new species and new records from the superfamily Pyraloidea (Rao & Sivaperuman, 2021;Singh et al 2020;Mathew, 2006;Raha et al 2017;Murthy et al 2015). A catalogue of Indian Pyraloidea was published recently, and it included 1,695 described species of Pyraloidea moths distributed among 509 genera (Singh et al 2022).…”
Section: Introductionmentioning
confidence: 99%